TINDAK PIDANA PENELANTARAN RUMAH TANGGA MENURUT UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA (Studi Putusan Mahkamah Agung Nomor 467K/Pid.Sus/2013) - Fitriani Fitriani; Mahmud Mulyadi; Muhammad Ekaputra; Chairul Bariah (Universitas Sumatera Utara, 2015)
ABSTRACT Criminal cat on neglecting a family is the fourth violence in Law No. 23/2004. Law on PKDRT does not provide systematic qualification about an action which is categorized as the act of neglecting. Today, imprisonment is considered the moist effective way to cope with the incidence of criminal act.The result of the research showed that criminal act of neglecting a family included not provide life for the family such as not supporting his children financially and not taking care of the family, especially when the family members were sick, not taking responsibility for the family members like economic neglect prohibiting them to get jobs, not fulfilling his obligation like taking something without the knowledge and the approval of the owner, and taking by force and/or manipulating the family members’ property. Imprisonment or fine is not appropriate imposed on the perpetrator who has neglected his family since it does not mean anything for the victim. He has to compensate the loss. One year imprisonment charged by judex juris judge is considered not appropriate; it seems that the judge did not consider the facts found in the hearing and Article 4, point d of Law of PKDRT Keywords: Criminal Act, Neglecting, Violence in Household